Purification of long helical capsid of newcastle disease virus from Escherichia coli - Yap, Chee Fai (2013)
The truncated version of nucleocapsid (N) protein of Newcastle disease virus (NDV) expressed in Escherichia coli, NPΔc375 self-assembles into relatively long herringbone-like particles. This truncated protein is vulnerable to endogenous host cell proteases. In order to limit the degradation and improve the production yield of recombinant NPΔc375, a bioinformatics programme, PeptideCutter was used to predict the possible endogenous proteases that led to the NPΔc375 degradation. The size of the degraded bands of the NPΔc375 of NDV on Western blots was analyzed by using the Quantity One software to predict the potential proteases cleavage sites on NPΔc375 amino acid sequence. The possible proteases that degrade NPΔc375 are serine and metalloproteases. Serine and metalloprotease inhibitors, namely phenylmethylsulfonyl fluoride (PMSF) and ethylenediaminetetraacetic acid (EDTA) were therefore employed to inhibit the endogenous proteolytic activities. Combination of the mentioned protease inhibitors at their optimal concentration was found to have a synergistic effect and resulted in about 2.1-fold increase in the NPΔc375 yield. When tested with enzyme-linked immunosorbent assay (ELISA), the purified NPΔc375 treated with protease inhibitors was found to retain its reactivity against chicken anti-NDV antisera. In addition, they assembled into ring-like, short and long herringbone-like structures when examined under a transmission electron microscope (TEM). These imply that both the antigenicity and the particle forming capacity of the NPΔc375 were preserved after being treated with protease inhibitors. The conventional sucrose density gradient ultracentrifugation has been stated to be tedious and time consuming in the purification of NDV N protein. With the intention of improving the purification efficiency, the recombinant NPΔc375 of NDV was purified with a packed bed anion exchange chromatography (AEC) from clarified E. coli homogenate. Packed bed AEC permits the purification processes to be completed in a shorter duration with lesser number of unit operations than that of sucrose density gradient ultracentrifugation. There was 76.3% of NPΔc375 from the clarified E. coli homogenate adsorbed to the anion exchanger at the optimal binding pH (pH 6). An optimal desorption of the bound NPΔc375 was accomplished by applying 50 mM Tris-HCl buffer at pH 7 in the presence of 0.5 M NaCl. The purification of NPΔc375 of NDV by employing a pre-packed AEC has resulted in a 51.4% recovery of NPΔc375 from the clarified feedstock with a purity and purification factor of 76.7% and 6.5, respectively. The antigenicity and the self-assembly property of the purified NPΔc375 were preserved throughout the whole purification process as proven by ELISA and TEM analysis, respectively. The helical structure formed was as long as 490 nm and 22-24 nm in diameter.